Assessment of soil heavy metal pollution in a former mining area - before and after the end of mining activities - Lenka Demková; Tomáš Jezný; Lenka Bobuľská (Soil and Water Research, 2017)
Toxicity and persistence of heavy metals, which are accumulated in the environment as the result of diverse industrial activities, represent serious environmental problem worldwide. The intense mineral extraction in mining areas has produced a large amount of waste material and tailings, which release toxic elements to the environment. The aim of the study was to determine in two time horizons (1997, 2015) the heavy metal contents of samples derived from ten sampling sites located in the former mining area of Central Spiš (Slovakia). In order to compare the level of contamination, the contamination factor (Cif), degree of contamination (Cd), and pollution load index (PLI) were computed. Spearman's correlation coefficient was used in order to detect the relationships among heavy metals. A serious situation was found for Hg, Zn, and Cd, which exceeded limit values at all sampling sites within both studied years. In 1997, the average values of contamination factor have shown very high contamination with all studied heavy metals, and moderate contamination with Co. In 2015, the study area was classified as very highly contaminated with As, Hg, Zn, Cu, considerably contaminated with Ni, Cr, Pb, and Cd, while Co contamination was not detected. Since 1997 till 2015 the pollution load index decreased by about 38%, nevertheless even then almost all sampling sites were classified as heavily polluted. Despite the fact that mining activities were stopped or limited at the beginning of the 21st century, the presence of heavy metals in soils remains at a serious level. The high level of contamination is a result of heavy metal persistence and non-biodegradability.